Value of contrast CT in combination with PET/CT in mesothelioma staging: Optimal protocol for initial assessment - Mohamed Houseni (The Egyptian Journal of Radiology and Nuclear Medicine, 2017)
Purpose: To assess the value of contrast enhanced CT (ceCT) when added to positron emission tomography combined with the standard low-dose non-contrast CT (PET/CT) protocols for staging patients with malignant pleural mesothelioma (MPM). Methods: Retrospective analysis of 47 patients with pathologically proved MPM. All patients underwent PET/CT with low dose CT followed by ceCT. PET/CT and ce-CT were evaluated separately then in combination. All the results were validated either by histopathology and/or clinical-radiological follow-up. Staging was performed based on TNM system. Results: For T-stage, the sensitivities for PET/CT, ceCT and combined PET/CT-ceCT were 89.1%, 86.9%, and 97.5%, respectively, p = 0.04. Regarding nodal stage, the sensitivity, specificity and accuracy for PET/CT were 88.5%, 90.5%, and 89.4%; for ceCT 73.1%, 95.2% and 82.9%; and for PET/CT-ceCT 96.2%, 95.2% and 95.7%, respectively. PET/CT-ceCT significantly associated with the sensitivity, p = 0.05. Considering the metastatic disease, the sensitivity, specificity and accuracy for PET/CT were 81.3%, 96.8%, and 91.5%; for ceCT 56.3%, 90.3% and 78.7%; and for PET/CT-ceCT 93.8%, 96.8% and 95.7%, respectively. PET/CT-ceCT significantly improved the sensitivity (p = 0.03) and accuracy (p = 0.02). Furthermore, combined PET/CT-ceCT significantly identified patients not suitable for surgery. Conclusion: The addition of ceCT to PET/CT protocol has significantly contributed to the staging of MPM.